1998
DOI: 10.1108/09526869810216052
|View full text |Cite
|
Sign up to set email alerts
|

Comparing public and private hospital care service quality

Abstract: The study applies the principles behind the SERVQUAL model and uses Donabedian’s framework to compare and contrast Malta’s public and private hospital care service quality. Through the identification of 16 service quality indicators and the use of a Likert‐type scale, two questionnaires were developed. The first questionnaire measured patient pre‐admission expectations for public and private hospital service quality (in respect of one another). It also determined the weighted importance given to the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 9 publications
6
73
1
5
Order By: Relevance
“…Our study indicates the need for better patient handling techniques by dental healthcare staff, improvement in the clinic infrastructure and increased professionalism through timeliness by dental personnel. This is similar to the previous report by Camilleri and O'Callaghan [33] who evaluated Maltese public and private hospitals using a similar study instrument as ours. They found that three most significant service quality indicators in the opinion of patients were related to the hospital environment, personalised service and professional care.…”
Section: Discussionsupporting
confidence: 92%
“…Our study indicates the need for better patient handling techniques by dental healthcare staff, improvement in the clinic infrastructure and increased professionalism through timeliness by dental personnel. This is similar to the previous report by Camilleri and O'Callaghan [33] who evaluated Maltese public and private hospitals using a similar study instrument as ours. They found that three most significant service quality indicators in the opinion of patients were related to the hospital environment, personalised service and professional care.…”
Section: Discussionsupporting
confidence: 92%
“…The researchers, Tomes and Ng (1995) conducted content analysis and concluded that there are eight dimensions in total, such as empathy, understanding of the disease, relationship of mutual respect, nutrition, dignity of the hospitalized, natural environment and religious needs. Camilleri and O'Callaghan (1998) argue that parameters such as professional and technical care, personalization of services, cost, environment, patient comfort, nutritional accessibility are the appropriate dimensions of hospital quality measurement. Andaleeb (1998), on the other hand, limits them to five dimensions, such as communication, cost, installation, competence, and behavior.…”
Section: Dimensions Of Healthcare Qualitymentioning
confidence: 99%
“…After a thorough study of the existing literature, it was considered that the dimensions that adequately describe the overall quality of hospital care are those supported by Padma et al (2009Padma et al ( , 2010, which are broken down as follows: a. Infrastructure: This includes the degree of cleanliness and comfort of the room, the degree of hospital overall safety, the level of availability of the required drugs at the right time, the level of availability of doctors and nurses, the level of availability of medical equipment and good working condition (Thompson 1983, Parasuraman et al, 1988, Reidenbach and Sandifer-Smallwood 1990, Tomes and Ng 1995, Camilleri and O'Callaghan 1998, Andaleeb 1998, Chowdhary and Prakash 2007, Walters and Jones 2001, Arasli et al, 2008, Zineldin 2006, Duggirala et al, 2008, Padma et al, 2010, Itumalla et al 2014 Gronroos (1990) introduced a comprehensive list of six criteria for the proper understanding of service quality, such as professionalism and skills, attitudes and behavior, accessibility and flexibility, reliability and validity, recovery, reputation and solvency. Padma et al (2010) argue in their research that staff quality is the main dimension that affects patient satisfaction.…”
Section: Dimensions Of Healthcare Qualitymentioning
confidence: 99%
“…Several studies to assess perceived service quality have been performed in the healthcare industry. Some have been done regarding public healthcare (Aagja, & Garg, 2010, Camilleri, & O'Callaghan, 1998 while others address private healthcare (Camilleri, & O'Callaghan, 1998). The fact is that specific needs emerge daily and are associated with basic necessities of life.…”
Section: Organizational Characteristics Of the Elderly Homecare Servimentioning
confidence: 99%